2013
DOI: 10.1021/cs400147d
|View full text |Cite
|
Sign up to set email alerts
|

Origins of Unusual Alcohol Selectivities over Mixed MgAl Oxide-Supported K/MoS2 Catalysts for Higher Alcohol Synthesis from Syngas

Abstract: A series of MoS2 catalysts supported on Mg/Al hydrotalcite-derived mixed-metal oxide (MMO) supports promoted with K2CO3 is used for alcohol synthesis via CO hydrogenation. Alcohol selectivities are found to vary greatly when the Mo is loaded on the support at 5 wt % compared with 15 wt % Mo samples, all with a Mo/K atomic ratio of 1:1. The most striking difference between the catalysts is the comparatively low methanol and high C3+ alcohol selectivities and productivities achieved with the 5% Mo catalyst. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 113 publications
6
66
0
Order By: Relevance
“…These studies showed that catalytic activity is enhanced by dispersing the MoS 2 over a support and that Mo-support interactions can affect the reactivity and product distribution of the catalyst by facilitating alcohol reaction pathways. Recently, Morrill et al [37,38] developed new potassium promoted MoS 2 catalysts supported on a mixed Mg/Al oxide (MMO) support, derived from a hydrotalcite, that strongly perturbed the product distribution toward higher alcohols. The intrinsically basic properties of the support were suggested to promote alcohol-forming reactions, unlike common acidic c-alumina [39][40][41][42] known to promote alcohol dehydration and subsequent hydrocarbon formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies showed that catalytic activity is enhanced by dispersing the MoS 2 over a support and that Mo-support interactions can affect the reactivity and product distribution of the catalyst by facilitating alcohol reaction pathways. Recently, Morrill et al [37,38] developed new potassium promoted MoS 2 catalysts supported on a mixed Mg/Al oxide (MMO) support, derived from a hydrotalcite, that strongly perturbed the product distribution toward higher alcohols. The intrinsically basic properties of the support were suggested to promote alcohol-forming reactions, unlike common acidic c-alumina [39][40][41][42] known to promote alcohol dehydration and subsequent hydrocarbon formation.…”
Section: Introductionmentioning
confidence: 99%
“…The studies indicated that MMO supports yielded high C 3+ OH selectivity influenced by Mo-MMO interactions, but generally also yielded low catalytic productivity. It has further been shown that the Mo:MMO ratio greatly affected the reaction selectivity, while catalyst preparation methods had little impact on this parameter [38].…”
Section: Introductionmentioning
confidence: 99%
“…The detailed procedure was described in our previous publications [16,29]. In brief, a 150mL-mixed Table 1S in Supplementary Materials).…”
Section: Preparation and Characterization Of The Catalystsmentioning
confidence: 99%
“…Indeed, the binding energy of C 1s is presumably composed of two overlapping peaks at 284.5 and 285.8 eV. The first peak is assigned from the carbons in contaminated organic product of spent samples while the higher binding value is characteristically assigned to carbonate anions (C = O, C -O bond) in the interlayered spaces [29,36,47,49,50].…”
Section: Xps Analysismentioning
confidence: 99%
See 1 more Smart Citation